Pengaruh Tipografi Pada Logo Coca-Cola Dalam Membangun Brand Awareness - Isdriani Isdriani Isdriani; M Syaifullah Islamudin (Peneliti.net, 2023)
Coca-Cola logo in building brand awareness among consumers and the influence of consistent typographical design to differentiate the brand from competitors and develop brand loyalty. The method used in this research is descriptive qualitative research method. The results of the study show that the typography used in the Coca-Cola logo has an important role in building brand awareness. The distinctive and memorable Spencerian Script typography has helped Coca-Cola to differentiate itself from competitors and increase brand awareness among consumers. In addition, consistent use of typography has helped Coca-Cola to build emotional connections with consumers and create strong consumer loyalty. Research also shows that typography can influence consumer perceptions of brands in terms of credibility, trust and product quality. In this case, the right typography can help Coca-Cola build a strong brand image and influence consumers' positive perceptions of the brand.